Application of silicene, germanene and stanene for Na or Li ion storage: A theoretical investigation - Mortazavi, Bohayra; Dianat, Arezoo; Cuniberti, Gianaurelio (Giovanni); Rabczuk, Timon (Electrochimica Acta, 2016)
Silicene, germanene and stanene likely to graphene are atomic thick material with interesting properties. We employed first-principles density functional theory (DFT) calculations to investigate and compare the interaction of Na or Li ions on these films. We first identified the most stable binding sites and their corresponding binding energies for a single Na or Li adatom on the considered membranes. Then we gradually increased the ions concentration until the full saturation of the surfaces is achieved. Our Bader charge analysis confirmed complete charge transfer between Li or Na ions with the studied 2D sheets. We then utilized nudged elastic band method to analyze and compare the energy barriers for Li or Na ions diffusions along the surface and through the films thicknesses. Our investigation findings can be useful for the potential application of silicene, germanene and stanene for Na or Li ion batteries.
CRIS-Team Scopus Importer:2023-03-20
Keywords: first-principles; germanene; Li ions; Silicene; stanene